MORPHOLOGICAL ANALYSIS BETWEEN PREFIX AND SUFFIX IN JACQUELINE HOWARD ARTICLE OF CNN - Risna Dewi Nurhayati; Lukman Arif Rahman (PROJECT (Professional Journal of English Education), 2024)
This study aims to find out the types of suffixes and to find out the frequently used prefixes and suffixes in CNN’s Jacqueline Howard's article titled "Eating A Plant-Based Diet Might Help Prevent Type 2 Diabetes, Study Suggests". In this research, the writer uses descriptive qualitative methods by conducting 3 steps in analyzing the text taken from the CNN website. The first step is searching and collecting the data, the next is analyzing the data, and the last is classify the words that have been analyzed according to this kind. The method of collecting in this research is taken from CNN’s website. In Jacqueline Howard's article for CNN, there are prefixes and suffixes. Data appears in various forms of prefix and suffix. The total data prefix in Jacqueline Howard's article for CNN is 11. From the data that has been analyzed, the writer found four types of suffix in Jacqueline Howard's article for CNN. The total number of data words of Noun Suffix in text is 5. The data words of Verbal Suffix in text are 3, the data words of Adjectival Suffix in text are 5, and the last data word of Adverbial Suffix in text is 7. Then the writer also concluded that the frequently used prefix in Jacqueline Howard's articles is the prefix "In-." And the type of suffix often used is the word adverbial, like-ly.